Biossolubilização de fósforo proveniente de concentrado de rocha fosfática por Trichoderma harzianum em diferentes biorreatores - Cabral, Bruna Vieira (2016)
The availability of nutrients for plants is a decisive factor for their development and growth. Phosphorus is one of the most important nutrients for the agricultural crops being a limiting factor for plant growth by influencing the supply of energy needed for metabolic processes. One of the main problems related to nutrient absorption by the plants is due to the fact that a large portion soluble inorganic phosphate applied to the soil as compost, is rapidly immobilized in the forms of insoluble phosphate. One approach to minimizing this problem is the use of microorganisms, especially some species of fungus effective for phosphorus release by the production of acids, mineralization or phosphatase production. This work aimed to study the phosphorus biosolubilization from phosphate rock concentrate of Trichoderma harzianum on different configurations of reactors. Through quantitative classification evaluated the solubilization capacity of 16 fungal isolates previously collected and later the influence of the glucose concentration, rock phosphate concentrate and inoculum in liquid selective synthetic medium in conical bench reactors. It was also studied the biosolubilization process in air-lift reactor containing phosphate rock concentrate continuing the process in conical bench reactors. The process was also study in series, in which organic acids were produced in air-lift reactor and solubilization occurred in conical bench reactor. Variables such as volumetric air flow, temperature, recycle of the reaction medium, inoculum concentration, glucose and phosphate rock concentrate were optimized in air-lift reactor. It was studied further rotary reactor using sugarcane bagasse as support for Trichoderma harzianum growth evaluating the ratio mass of biomass/volume of liquid synthetic medium and wet aeration. In air-lift reactor at 28 ± 3 ° C with aeration of 0.5 VVM, recycle of the reaction medium to 200 ml/min, initial cell concentration of 3.7 g/L phosphate rock concentrate 5 g/L and glucose is restored to 10 g/L was obtained on fourth day of operation a phosphorus solubilization equal to 40.47%. The continuous process of phosphorus solubilization on conic bench reactors solubilized 43.43% of the total phosphorus adding inoculum with an initial concentration of 3.1 g/L glucose and phosphate rock concentrate at 5 g/L to the reaction medium produced in fourth day of air-lift reactor operation containing concentrate rock phosphate. In the batch process consisting of the production of organic acids in air-lift reactor followed by phosphorous solubilising process on conic bench reactors, 34.88% of the total phosphorus was provided on the third day the process employing glucose and phosphate rock concentrate at 10 and 5 g/L, respectively. Finally in rotary reactors were obtained maximum values of solubilization and production of organic acids equal to 37.83% and 8.59 μ.mol/ml, respectively, for the relation of 39.53 g of cane bagasse/50 ml of liquid selective synthetic medium (glucose and phosphate rock concentrate at 5g/L). By employing wet aeration the biossolubilization process in rotating reactors by Trichoderma harzianum the maximum solubilization equal to 48.16% was found using volumetric flow of compressed air of 8.06 VVM, maintaining the humidity at 14.58% ± 0.3. By analyzing the process time and the maximum percentage of phosphorus biossolubilization reached the best results were achieved in the reactor rotating drum type.